Genetic variation in functional traits influences arthropod community composition in aspen (Populus tremula L.). - Kathryn M Robinson (Public Library of Science (PLoS), 2012)
We conducted a study of natural variation in functional leaf traits and herbivory in 116 clones of European aspen, Populus tremula L., the Swedish Aspen (SwAsp) collection, originating from ten degrees of latitude across Sweden and grown in a common garden. In surveys of phytophagous arthropods over two years, we found the aspen canopy supports nearly 100 morphospecies. We identified significant broad-sense heritability of plant functional traits, basic plant defence chemistry, and arthropod community traits. The majority of arthropods were specialists, those coevolved with P. tremula to tolerate and even utilize leaf defence compounds. Arthropod abundance and richness were more closely related to plant growth rates than general chemical defences and relationships were identified between the arthropod community and stem growth, leaf and petiole morphology, anthocyanins, and condensed tannins. Heritable genetic variation in plant traits in young aspen was found to structure arthropod community; however no single trait drives the preferences of arthropod folivores among young aspen genotypes. The influence of natural variation in plant traits on the arthropod community indicates the importance of maintaining genetic variation in wild trees as keystone species for biodiversity. It further suggests that aspen can be a resource for the study of mechanisms of natural resistance to herbivores.